General Synthetic Approach to Rotenoids via Stereospecific, Group-Selective 1,2-Rearrangement and Dual SNAr Cyclizations of Aryl Fluorides - Matsuoka, Seiya; Nakamura, Kayo; Ohmori, Ken; Suzuki, Keisuke (Synthesis, 2019)
A general synthetic approach to rotenoids is described, featuring 1) stereospecific, group-selective 1,2-rearrangements of epoxy alcohols, and 2) SNAr oxy-cyclizations of aryl fluorides. The common intermediate epoxyketone, en route to (–)-rotenone and (–)-deguelin, was prepared from d-araboascorbic acid in five steps. Also described is the conversion of (–)-deguelin into oxidized congeners, (–)-tephrosin and (+)-12a-epi-tephrosin.
Keywords: isoflavonoid; rotenoid; semi-pinacol rearrangement; SNAr cyclization; total synthesis